2021
DOI: 10.12973/eu-jer.10.4.1881
|View full text |Cite
|
Sign up to set email alerts
|

Cyberslacking Behavior and Its Relationship with Academic Performance: A Study of Students in Indonesia

Abstract: <p style="text-align: justify;">Students are aware of the use of technology in the learning process, and they are generally referred to as digital natives. However, there are challenges associated with the availability of internet access as a learning process to both university students and teachers inside and outside the classroom. One of such challenges is students’ ability to access unrelated activities which is known as cyberslacking. In the education sector, this process refers to the use of technol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Based on the results obtained, it is possible to sustain that knowledge has been one of the fundamental pillars for the development of society and in the learning and recognition of natural and patrimonial spaces and resources [51,52]. In this sense, the technological developments obtained as a result of knowledge have been used as support in different contexts of society, including the educational and sustainable development context [53,54].…”
Section: Discussionmentioning
confidence: 90%
“…Based on the results obtained, it is possible to sustain that knowledge has been one of the fundamental pillars for the development of society and in the learning and recognition of natural and patrimonial spaces and resources [51,52]. In this sense, the technological developments obtained as a result of knowledge have been used as support in different contexts of society, including the educational and sustainable development context [53,54].…”
Section: Discussionmentioning
confidence: 90%
“…Some of the findings from this study revealed that the intention to engage in cyberslacking is influenced by the individual's attitude and desire to escape from academic responsibilities. A study from the Indonesian context by Margaretha, Monalisa, Mariana, Junita & Iskandar (2022) revealed that there is a significant relationship between one's ability to effectively engage in media multitasking and the level of self-regulated learning, in relation to engaging in cyberslacking activities, yet the distraction does not impact the performance of the students. This implies that students who exhibit challenges in maintaining focus, demonstrate disinterest in the subject matter, or are susceptible to distractions from their peers are more inclined to possess a favourable disposition towards engaging in cyberslacking.…”
Section: Cyberslackingmentioning
confidence: 99%
“…The educational literature reports that college students’ cyberslacking behaviors include checking emails, playing online games, using social networking websites, reading news, and shopping online [ 6 , 7 , 8 ]. Students’ cyberslacking behaviors may lead to negative consequences, such as distraction [ 2 ], smartphone addiction [ 9 ], and poor academic performance [ 10 ]. With easy access to mobile devices and wireless Internet in TEL, cyberslacking is increasingly noticeable among college students [ 2 , 11 ].…”
Section: Introductionmentioning
confidence: 99%